Resilience of the European Union Economies. An Analysis of the Granger Causality at the Level of the Gross Domestic Product - Mihai Păunică; Alexandru Manole; Cătălina Motofei; Gabriela-Lidia Tănase (Amfiteatru Economic)
Gross Domestic Product (GDP) is one of the most important indicators that reflects the evolution and resilience of national economies. The importance of this macroeconomic indicator is growing in the current economic context, context in which international studies start to emphasize the importance of resilience and sustainable development and in which the GDP can be seen either as an obstacle to sustainability, or a tool to protect the environment and achieve the resilience and sustainability goals. Consequently, the authors consider that understanding the formation of the GDP and the elements that exert an influence on it, remains of vital importance for the economy of a country or group of countries. The objective of the paper is to see if some of the indicators that are used to determine the GDP, respectively final consumption expenditure of general government, final consumption expenditure of households, gross fixed capital formation, changes in inventories, external balance – goods, external balance – services, wages and salaries and, respectively, employers’ social contributions, together with two indicators of final energy consumption, are Granger causing the GDP. The results obtained will indicate whether GDP can be predicted at a highly accurate level, by using not only the previous values of the GDP, but also the previous values of determining variables, and will also contribute to highlight those elements that have such an impact on the GDP, in order to better estimate its evolution and to have the possibility to influence its future values.